Reflection of intense laser light from microstructured targets as a potential diagnostic of laser focus and plasma temperature. (2019) - Jarrett, J.; King, M.; Gray, R. J.; Neumann, N.; Döhl, L.; Baird, C. D.; Ebert, T.; Hesse, M.; Tebartz, A.; Rusby, D. R.; Woolsey, N. C.; Neely, D.; et al.
Abstract : The spatial-intensity profile of light reflected during the interaction of an intense laser pulse with a microstructured target is investigated experimentally and the potential to apply this as a diagnostic of the interaction physics is explored numerically. Diffraction and speckle patterns are measured in the specularly reflected light in the cases of targets with regular groove and needle-like structures, respectively, highlighting the potential to use this as a diagnostic of the evolving plasma surface. It is shown, via ray-tracing and numerical modelling, that for a laser focal spot diameter smaller than the periodicity of the target structure, the reflected light patterns can potentially be used to diagnose the degree of plasma expansion, and by extension the local plasma temperature, at the focus of the intense laser light. The reflected patterns could also be used to diagnose the size of the laser focal spot during a high-intensity interaction when using a regular structure with known spacing.